The kabuki theatre - Ernst, Earle (An East - West Center, 1974)
An authoritative guide.The book explains everything lucidly and painstakingly--the background, the facts, the emotions. Ernst shows us the theatre from the inside, with deep understanding of its meaning and purpose.